A Framework for Social Determinants of Health Integration in Population Health Management Systems - Prakash Easwaran (International Journal of Computational and Experimental Science and Engineering, 2026)
Traditional models of health care delivery mainly involve health care approaches while overlooking non-health issues that influence health care outcomes and health care expenditures. Social determinants of health relate to poverty, educational attainment, housing status, accessibility of transport, and food availability. Addressing such determinants requires systematic capabilities within population health management platforms. A dual-layer risk assessment framework provides comprehensive identification of social needs across populations. Community-level scoring leverages census tract geography and publicly available socioeconomic data. Six primary domains, including education, employment, income, transportation, housing, and food access, contribute to cumulative geographic risk calculations. Member-level assessments capture individual circumstances through structured screening instruments administered during care management encounters. Individual scores override community-level assignments when documented personal needs diverge from neighborhood averages. Risk stratification algorithms classify populations into tiered categories based on cumulative scores. High-risk individuals receive intensive care management with dedicated program enrollment. Medium-risk individuals receive educational materials and periodic monitoring. Configurable parameters enable organizational customization of scoring weights and threshold boundaries. Integration with community-based organization referral platforms enables closed-loop referral management. Electronic referral transmission and status tracking support regulatory compliance requirements. It translates disparate efforts within social care into structured and trackable interventions within healthcare populations.